The Urgency Of Quality Assurance For Educational Customers - Setiawan, Bagus; Rahman, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The aim of this research is to find out how urgent quality assurance is for education customers. This research method uses literature study by collecting from various reading sources such as e-books, journals or examining online literature. The research results found that Quality Assurance is a quality guarantee offered by an institution. In line with the times, quality assurance has also been developed by educational institutions. Quality assurance carried out by educational institutions is more oriented towards guaranteeing the quality of education offered to educational customers. There are several efforts to improve the quality of education through quality assurance, including good quality assurance planning, implementation of quality assurance planning and evaluation of quality assurance carried out by educational institutions